2021
DOI: 10.1021/acsearthspacechem.1c00026
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Attainment of Isotopic Equilibrium after Mercury Reduction by Ferrous Iron Minerals and Isotopic Exchange between Hg(II) and Hg(0)

Abstract: We examined Hg stable isotope fractionation after the partial reduction of Hg­(II) to Hg(0) by the siderite and green rust of ferrous iron minerals. The fractionation of Hg isotopes in closed-system experiments followed an equilibrium fractionation model, with Hg­(II) enriched in heavier isotopes. The results indicated isotopic fractionation (δ202HgII–δ202Hg0) of 2.43 ± 0.38 and 2.28 ± 0.40‰ for the siderite and green rust experiments, respectively. Experiments were also performed to determine if the rapid att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 53 publications
1
20
1
Order By: Relevance
“…Equilibrium isotope fractionation between Hg 0 and Hg 2+ results in more positive δ 202 Hg values in the Hg 2+ pool, 83,85,86 which could play a role in the observed Hg stable isotope data in SCB1. The δ 202 Hg value of the bulk sample will become more positive only if there has been Hg 0 loss from the solid-phase (evaporation unfavourable in subsurface samples).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Equilibrium isotope fractionation between Hg 0 and Hg 2+ results in more positive δ 202 Hg values in the Hg 2+ pool, 83,85,86 which could play a role in the observed Hg stable isotope data in SCB1. The δ 202 Hg value of the bulk sample will become more positive only if there has been Hg 0 loss from the solid-phase (evaporation unfavourable in subsurface samples).…”
Section: Resultsmentioning
confidence: 93%
“…This fractionation to heavier isotopes should be enhanced when we consider that Hg 2+ species are also enriched in heavier isotopes by equilibrium isotope fractionation between Hg 0 and Hg 2+ . 85,86 Thus, evaporative losses of Hg 0 from the solid-or liquid-phase to soil airspaces or even groundwater well shas would result in further enrichment of remaining solid and liquid-phase pools in heavy isotopes.…”
Section: †) There Was Nomentioning
confidence: 99%
See 1 more Smart Citation
“…26,46 Adsorption and/or desorption processes may therefore have affected MDF by at most 0.62‰ 26,46 but probably had a limited effect on MIF in these experiments. While isotopic exchange due to aqueous-phase Hg(II)−Hg(0) equilibration has been observed in nonpurged, closed-system experiments, 28 such Hg isotope fractionation is unlikely to have exerted a major influence in our purged reactor experiments in which Hg(0) was continuously removed.…”
Section: Resultsmentioning
confidence: 99%
“…Stable isotopes of Hg exhibit both mass-dependent fractionation (MDF, represented by δ 202 Hg) and mass-independent fractionation (MIF) during Hg transformations under various environmental conditions. MIF includes odd-mass-number MIF (odd-MIF), represented by Δ 199 Hg and Δ 201 Hg, and even-mass-number MIF (even-MIF), represented by Δ 200 Hg and Δ 204 Hg. Prior studies have shown that MDF is induced by several Hg transformation and transport processes, , but large values of odd-MIF result primarily from photochemical reactions under various environmental conditions. ,, …”
Section: Introductionmentioning
confidence: 99%